PENGARUH PERSEPSI KUALITAS DAN KESADARAN MEREK TERHADAP LOYALITAS MEREK DENGAN CITRA MEREK SEBAGAI VARIABEL MEDIASI PADA PENGGUNA LAMPU LED HANNOCHS DI BANDA ACEH - Mitra Musapat, Saed Armia (Departemen Manajemen, 2018)
This study aims to determine the influence of perceived of brand awareness and quality on brand loyalty with brand image as a mediation variable. Samples used in this study are 100 respondents who are users of LED lights Hannochs Banda Aceh. Purposive Sampling is used as a sampling technique. Partial Least Square (PLS) analysis method is used as a method of analysis to determine the effect of the variables involved. The results of this study indicate that the Perceived Quality and Brand Awareness affect the brand loyalty. In addition, the results of the Brand Image variaby act as a partial mediation on the variable of Perceived Quality on Brand Loyalty, and Brand Image also serves as a full mediation on the Brand Awareness variable on Brand Loyalty. The higher the perceived Quality and Brand Awareness, The higher the Brand Image, the stronger the brand Loyalty owned by the consumer.Keywords: Perceived Quality, Brand Awareness,Brand Image, Brand Loyalty,LED HANNOCHS